System of System Failures - Nakamura, Takafumi (IntechOpen, 2018)
This book provides the application of praxises in the field of engineering safety by learning from previous system failures. And it addresses the most recent developments in the theoretical and practical aspects of these important fields, which, due to their special nature, bring together in a systematic way, many disciplines of engineering, from the traditional to the most technologically advanced. The authors of these chapters are involved in using the system thinking and system engineering approaches at the scale of increased complexity and advanced computational solutions to such systems. The chapters cover the areas such as failure assessment in aeronautical engineering, seismic resistance of offshore pipeline engineering, electrical engineering, critical infrastructure failure, and system of system theory.